2018
DOI: 10.1038/s41598-017-18800-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study reveals candidate genes influencing lipids and diterpenes contents in Coffea arabica L

Abstract: Lipids, including the diterpenes cafestol and kahweol, are key compounds that contribute to the quality of coffee beverages. We determined total lipid content and cafestol and kahweol concentrations in green beans and genotyped 107 Coffea arabica accessions, including wild genotypes from the historical FAO collection from Ethiopia. A genome-wide association study was performed to identify genomic regions associated with lipid, cafestol and kahweol contents and cafestol/kahweol ratio. Using the diploid Coffea c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 65 publications
4
57
0
1
Order By: Relevance
“…Among the implemented ML-GWAS methods, pLARmEB and ISIS EM-BLASSO detected the higher number of significant QTNs. The same observation was made in the recent study (Sant'ana et al, 2018 ), who reported a high number of trait-associated SNPs using two methods. On the other hand (Ma et al, 2018 ), acknowledge the robustness of ISIS EM-BLASSO than the other three methods (FASTmrEMMA, pLARmEB, mrMLM).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Among the implemented ML-GWAS methods, pLARmEB and ISIS EM-BLASSO detected the higher number of significant QTNs. The same observation was made in the recent study (Sant'ana et al, 2018 ), who reported a high number of trait-associated SNPs using two methods. On the other hand (Ma et al, 2018 ), acknowledge the robustness of ISIS EM-BLASSO than the other three methods (FASTmrEMMA, pLARmEB, mrMLM).…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, although, no SNP significantly associated QTNs were identified for cohesiveness using SL-GWAS and mrMLM methods, we detected putative genomic regions underlying COH using three other ML-GWAS methods. Multi-locus GWAS has gained popularity with a growing number of studies reporting the use of this approach (Misra et al, 2017 ; Ma et al, 2018 ; Sant'ana et al, 2018 ; Zhang et al, 2018 ) to perform marker-trait association. Some of the distinct advantages of multi-locus GWAS over single-locus GWAS are their power, accuracy in QTN effect estimation, reduced rate of false positives (Wang et al, 2016 ; Tamba et al, 2017 ; Ma et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…With its relatively small, diploid, sequenced and annotated genome, Coffea canephora is highly compliant with genomic‐based breeding approaches using Genome Wide Association Studies (GWAS). Thanks to the rapid development of genomic resources and the publication of the reference genome (Denoeud et al ., ), third‐generation markers based on single‐nucleotide polymorphisms (SNPs) have gradually been identified and assayed in Coffea , particularly in C. arabica (Sant'Ana et al ., ; Tran et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…primary and secondary metabolites and enzyme activities) (Wu et al, 2018(Wu et al, , 2016Fusari et al, 2017). Regarding lipid metabolism, a number of GWAS have been reported, for instance in Arabidopsis, maize, coffee, and canola, resulting in the identification of new enzymes and regulators (Riedelsheimer et al, 2013;Li et al, 2019;Sant'Ana et al, 2018;Gacek et al, 2017). These studies focused on lipid levels under optimal growth conditions.…”
Section: Introductionmentioning
confidence: 99%